The Development of Digital Audio Coding - Guo Ke (Tongxin xuebao)
The psychoacoustic models used in perceptnal audio coding are described. The algorithm and realtime hardware implement complexity of MPEG/Audio,Dolby AC-2 ,and AC-3 are introduced.The result of the MPEG/Audio multichannel subject listening tests are introduced also.